2020
DOI: 10.4103/jips.jips_50_20
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of antimicrobial potential of irreversible hydrocolloid impression material incorporated with chitosan

Abstract: Aim: To evaluate the antimicrobial potential of irreversible hydrocolloid impression material manipulated using chitosan impregnated solution at various time intervals. Setting and Design: Evaluative invivo study design. Materials and Methods: Maxillary impressions made for 20 dentulous volunteers using irreversible hydrocolloid impression material manipulated using distilled water as control and using 1% chitosan impregnated solution as test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…e result of the study coincided with previous studies that had demonstrated the antibacterial property of Chitosan and nano chitosan particles. [16][17][18][19][20][21][22][23][24] Chitosan exhibited potent antimicrobial properties against cariogenic bacteria when added to dentifrices, mouthwashes, composite resins, orthodontic bonding agents, and impression materials without affecting their mechanical and clinical properties. [16][17][18][19][20][21][22][23][24] Chitosan acts against bacteria by inhibiting the bacterial enzymes, causing chelation of metal ions and forming polyelectrolyte complexes on the bacterial cell wall.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…e result of the study coincided with previous studies that had demonstrated the antibacterial property of Chitosan and nano chitosan particles. [16][17][18][19][20][21][22][23][24] Chitosan exhibited potent antimicrobial properties against cariogenic bacteria when added to dentifrices, mouthwashes, composite resins, orthodontic bonding agents, and impression materials without affecting their mechanical and clinical properties. [16][17][18][19][20][21][22][23][24] Chitosan acts against bacteria by inhibiting the bacterial enzymes, causing chelation of metal ions and forming polyelectrolyte complexes on the bacterial cell wall.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24] Chitosan exhibited potent antimicrobial properties against cariogenic bacteria when added to dentifrices, mouthwashes, composite resins, orthodontic bonding agents, and impression materials without affecting their mechanical and clinical properties. [16][17][18][19][20][21][22][23][24] Chitosan acts against bacteria by inhibiting the bacterial enzymes, causing chelation of metal ions and forming polyelectrolyte complexes on the bacterial cell wall. [17,[25][26][27][28][29][30] is specific action of chitosan against S. mutans and L. acidophilus may be due to the presence of more anionic peptidoglycan and Teichoic acid in the cell wall of gram-positive bacteria that interact with the cationic amino group of chitosan leading to cell death.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, it is critical to consider the sides that may be elaborated in the fabrication of prosthesis, one of which is elastomeric impression material [8]. The impression materials used to replicate the shape of the teeth and surrounding structures [9]. This delivers a transmission of highly infectious pathogens such as hepatitis B and C among others [10].…”
Section: Introductionmentioning
confidence: 99%